Comparison of The Electrode Configuration of The Resistivity Geoelectric Method for Landslide Analysis on Highway Suban, Bandar Lampung: Analisis Kelongsoran dengan Metode Geolistrik Konfigurasi Wenner-Schlumberger dan Wenner-Alpha di Jalan Raya Suban Bandar Lampung - Rafi Rilo Pambudi; Muhammad Nurul; Winona Putri Prihadita; Rahmi Mulyasari (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
Jalan Raya Suban Bandar Lampung is located on the physiography of Bukit Barisan which is influenced by the movement of the Sumatran Fault, causing morphological conditions in the form of hills and steep slopes. This condition triggers the occurrence of disasters, one of which is landslides. In this study, the lithology of subsurface rocks and slides in the landslide-prone zone was examined using the Wenner-Schlumberger and Wenner-Alpha configuration geoelectrics. The Wenner-Schlumberger configuration has deeper penetration but lower resolution subsurface images, while the Wenner-Alpha configuration has less deep penetration but lower resolution surface images. The use of these two configurations is to take advantage of the advantages and reduce the disadvantages of each configuration in landslide analysis. The measurement results in the Wenner-Schlumberger and Wenner-Alpha configurations identified that the upper layer consists of weathered rock associated with clay tuff and sandy tuff with a resistivity of 1 m – 95.6 m, the second layer is clay sand from the Campang Formation with a resistivity value of 95.6 m – 250 m and the third layer is a mixture of breccia and igneous rock from the Tarahan Formation with a resistivity value of more than 250 m. The clay-sand layer was identified as the slip plane in the study area